THEME VARIATIONS IN THE SUBTITLING OF PENGABDI SETAN THE MOVIE: A STUDY OF TRANSLATION TECHNIQUES - Dhea Destyana, - (2019)
This study aims to figure out how the translator attempted to maintain equivalent meanings in terms of choice of theme in the subtitling of the movie Pengabdi Setan. This study also investigates how the translator's choice of themes in the target language (TL) is viewed from the concepts of translation techniques as proposed by Molina and Albir (2002). This study uses descriptive qualitative as research design. Findings of the analysis show that the translator attempted to maintain equivalent meanings through unshifting and shifting of themes which resulted in theme variations. As viewed from the concepts of translation techniques, 12 out of 18 techniques were employed to translate the themes of the clauses so as to deliver as closely equivalent meanings to that in the source language (SL). This study shows how the translator plays with the structure of information in a text as an effort to make meanings equivalent in the target language.